Growth of fall armyworm, Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) fed on young maize colonized with endophytic fungus Beauveria bassiana from South Sumatra, Indonesia - DETYA ROSA FADDILAH; MARIESKA VERAWATY; SITI HERLINDA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Faddilah DR, Verawaty M, Herlinda S. 2022. Growth of fall armyworm, Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) fed on young maize colonized with endophytic fungus Beauveria bassiana from South Sumatra, Indonesia. Biodiversitas 23: 6652-6660. The aim of present research was to evaluate the seed treated effect of endophytic Beauveria bassiana isolated from soil and infected-host cadavers on the growth of S. frugiperda. The three isolates (TaBrPGA, LtApPGA, and TaTtLH) of B. bassiana identified molecularly were used for bioassay. The research confirmed that isolates of B. bassiana isolated from soil and infected-host cadavers of Lepidoptera were endophytic entomopathogenic fungus. All isolates of endophytic B. bassiana caused negative effects on the growth of S. frugiperda larvae. TaTtLH isolate of B. bassiana was the most pathogenic isolate (73% of larvae mortality) among the other isolates. B. bassiana in seed treatment could retard the growth of S. frugiperda larvae, pupae, and adults. The endophytic B. bassiana could also kill the pupae and adults of S. frugiperda, and decrease the pupae and adult emergence. Beauveria bassiana could decrease 86% of adult emergence. Beauveria bassiana applied in seed treatment could protect since the stored corn seeds and the young maize plant against S. frugiperda. So, endophytic B. bassiana could be recommended to protect the stored corn seeds.